Intrapallidal injection of cannabidiol or a selective GPR55 antagonist decreases motor asymmetry and improves fine motor skills in hemiparkinsonian rats - Patricio, Felipe; Morales Dávila, Eliud; Patricio-Martínez, Aleidy; Arana Del Carmen, Nayeli; Martínez, Isabel; Aguilera, José; Perez-Aguilar, Jose Manuel; Limón, Ilhuicamina Daniel (Frontiers in Pharmacology, 2022)
Cannabidiol (CBD) presents antiparkinsonian properties and neuromodulatory effects, possibly due to the pleiotropic activity caused at multiple molecular targets. Recently, the GPR55 receptor has emerged as a molecular target of CBD. Interestingly, GPR55 mRNA is expressed in the external globus pallidus (GPe) and striatum, hence, it has been suggested that its activity is linked to motor dysfunction in Parkinson’s disease (PD). The present study aimed to evaluate the effect of the intrapallidal injection of both CBD and a selective GPR55 antagonist (CID16020046) on motor asymmetry, fine motor skills, and GAD-67 expression in hemiparkinsonian rats. The hemiparkinsonian animal model applied involved the induction of a lesion in male Wistar rats via the infusion of the neurotoxin 6-hydroxydopamine (6-OHDA) into the medial forebrain bundle via stereotaxic surgery. After a period of twenty days, a second surgical procedure was performed to implant a guide cannula into the GPe. Seven days later, lysophosphatidylinositol (LPI), CBD, or CID16020046 were injected once a day for three consecutive days (from the 28th to the 30th day post-lesion). Amphetamine-induced turning behavior was evaluated on the 14th and 30th days post-injury. The staircase test and fine motor skills were evaluated as follows: the rats were subject to a ten-day training period prior to the 6-OHDA injury; from the 15th to the 19th days post-lesion, the motor skills alterations were evaluated under basal conditions; and, from the 28th to the 30th day post-lesion, the pharmacological effects of the drugs administered were evaluated. The results obtained show that the administration of LPI or CBD generated lower levels of motor asymmetry in the turning behavior of hemiparkinsonian rats. It was also found that the injection of CBD or CID16020046, but not LPI, in the hemiparkinsonian rats generated significantly superior performance in the staircase test, in terms of the use of the forelimb contralateral to the 6-OHDA-induced lesion, when evaluated from the 28th to the 30th day post-lesion. Similar results were also observed for superior fine motor skills performance for pronation, grasp, and supination. Finally, the immunoreactivity levels were found to decrease for the GAD-67 enzyme in the striatum and the ipsilateral GPe of the rats injected with CBD and CID16020046, in contrast with those lesioned with 6-OHDA. The results obtained suggest that the inhibitory effects of CBD and CID16020046 on GPR55 in the GPe could be related to GABAergic overactivation in hemiparkinsonism, thus opening new perspectives to explain, at a cellular level, the reversal of the motor impairment observed in PD models.